Pengenalan Alat-Alat Teknik Mesin Sederhana Di Smp Negeri 1 Dolog Pardamean Simalungun - Jhon Sufriadi Purba; Niko Siburian (STMIK Royal, 2023)
Abstract : Today's modern era, the need for food has increased greatly among humans, it is comparable to the large population growth in today's world. In that case, simple technical equipment is needed which is widely used daily both for household needs and for the needs of farmers. Thus conventional equipment that is still used both among farmers, it will slow down the growth of agricultural production. For this reason, advanced technological equipment is needed, even today's modern ones, which are widely used in urban areas. Therefore, before using some of today's modern tools, it is necessary to provide knowledge education methods in the form of socializing the use of simple tools which are mostly used in educational settings as well as among farmers. So that the socialization of the introduction of these technical tools is very important at this time, to avoid misuse of these technical equipment, which is caused by a lack of knowledge of the community. By socializing these simple technical tools, it will result in a good understanding of all stakeholders at SMP Negeri 1 Dolog Pardamean, both teachers and students who will be able to recognize simple mechanical engineering tools that are used both at school and at home.Keywords : agriculture ; conventional ; introduction.Abstrak : Jaman Modern sekarang ini, kebutuhan bahan pangan sangat meningkat di kalangan manusia, itu sebanding dengan banyaknya pertumbuhan penduduk di dunia sekarang ini. Dalam hal itu, dibutuhkanlah peralatan teknik sederhana yang banyak dipergunakan sehari-hari baik bagi kebutuhan rumah tangga maupun kebutuhan para petani. Dengan demikian peralatan konvensional yang masih dipergunakan baik itu di kalangan para petani, itu akan memperlambat pertumbuhan produksi pertanian. Untuk itu, dibutuhkanlah peralatan teknologi yang maju bahkan yang modern sekarang ini yang sudah banyak dipergunakan di perkotaan. Oleh sebab itu, sebelum mempergunakan beberapa alat-alat modern yang sekarang ini, perlu diberikan metode pendidikan pengetahuan berupa sosialisasi penggunaan peralatan sederhana yang kebanyakan dipergunakan di lingkungan pendidikan maupun di lingkungan para petani. Sehingga sosialisasi pengenalan alat teknik tersebut merupakan yang sangat penting sekarang ini, untuk menghindari penyalah gunaan peralatan teknik tersebut, yang disebabkan kurangnya pengetahuan para masyarakat. Dengan dilakukannya sosialisasi alat-alat teknik sederhana tersebut, akan menghasilkan pemahaman yang baik diseluruh pemangku kepentingan yang di sekolah SMP Negeri 1 Dolog Pardamean baik guru maupun siswa yang akan dapat mengenal alat-alat teknik mesin sederhana yang dipakai baik itu di sekolah maupun di rumah.Kata Kunci : konvensional; pengenalan; pertanian